Understanding the Capabilities of ChatGPT for Learning and AI-Powered Assessment - Mohd. Arbab (International Journal of Education Sciences, 2026)
This paper investigates the integration of ChatGPT, a generative AI language model developed by OpenAI, into modern educational environments with a focus on its role in learning and assessment. ChatGPT’s ability to understand and generate human- like responses positions it as a powerful tool for enhancing personalized learning experiences, supporting students through interactive tutoring, and assisting educators in administrative and academic tasks such as content creation and automated grading. The study explores how ChatGPT facilitates critical thinking, provides immediate feedback, and helps in language learning, making it a versatile companion in both traditional and remote learning settings. Additionally, this paper reviews recent empirical studies and practical use cases that highlight the effectiveness of AI-powered assessment tools, including the generation of multiple-choice questions aligned with course outcomes. Alongside these benefits, the paper addresses major concerns such as data privacy, ethical considerations, over- reliance on AI, and the potential for academic dishonesty. A detailed analysis of usage trends and user statistics underscores ChatGPT’s rapid adoption in educational contexts. Ultimately, the paper presents a balanced perspective on the promises and pitfalls of incorporating ChatGPT in education, emphasizing the importance of responsible AI implementation and the need for robust academic policies to support ethical usage.
Keywords: Assessment; ChatGPT; Personalized learning; artificial intelligence; education